2021
DOI: 10.3390/ma14216560
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dry Sliding Wear and Friction Behaviour of Al7068/Si3N4/BN Hybrid Composites

Abstract: Hybrid aluminium metal matrix composites have the potential to replace single reinforced aluminium metal matrix composites due to improved properties. Moreover, tribological performance is critical for these composites, as they have extensive application areas, such as the automotive, aerospace, marine and defence industries. The present work aims to establish the tribological characteristics of Al7068/Si3N4/BN hybrid metal matrix composites prepared by stir casting route and studied using a pin-on-disc appara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…As a result, optimization methodologies may be the most practical alternative for determining the optimal processing conditions. Various techniques like Grey relational analysis (GRA), [9,10] genetic algorithm (GA), [26,27] artificial neural network (ANN), [28][29][30] response surface methodology (RSM), [31][32][33][34] fuzzy TOPSIS, [35,36] analysis of variance (ANOVA), [37] can be employed to address a range of these problems.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, optimization methodologies may be the most practical alternative for determining the optimal processing conditions. Various techniques like Grey relational analysis (GRA), [9,10] genetic algorithm (GA), [26,27] artificial neural network (ANN), [28][29][30] response surface methodology (RSM), [31][32][33][34] fuzzy TOPSIS, [35,36] analysis of variance (ANOVA), [37] can be employed to address a range of these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Subramanian et al [22] studied the tribological characteristics of Al7068/Si 3 N 4 /BN hybrid metal matrix composites processed by stir casting. The weight percentage of Si 3 N 4 and BN particles are varied as 0, 5, 10.…”
Section: Introductionmentioning
confidence: 99%
“…The laser surface alloying process in comparison to laser melting allows for a wider influence on the structure and properties of surface layers by adjusting the chemical composition of a liquid metal pool by the addition of the alloying elements. Previous studies in this field have shown that the addition of elements with high affinity to carbon in the laser alloying process may result in the formation of an in situ composite structure in the surface layer area [16][17][18][19]. An example of such an element is titanium, which when added in the laser alloying of a ductile cast iron surface causes the formation of high-hardness titanium carbides in the structure of the surface layer, which has a beneficial effect on the wear resistance of the surface.…”
Section: Introductionmentioning
confidence: 99%